Perancangan User Experience Aplikasi Creative Service Marketplace berbasis Mobile dengan Metode Design Thinking - Naufal Alif Aldhian; Herman Tolle (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
To help develop a business, digital marketing becomes one of the commonly used business strategies. In digital marketing, creativity is an important factor which leads to an increase in demand for creative industry services. However, there are problems faced by service providers (freelancers) and service seekers (business owners) in finding and searching for service providers according to their needs and prices, the lack of available service providers to be partners, the lack of options from service providers, the lack of transparency in the service execution process, the time of execution not in accordance with the agreement, and communication problems that cause results that do not meet expectations. Therefore, the design of a user experience application for a mobile-based creative service marketplace is carried out using the design thinking method to help developers solve these problems. Design thinking is used as a method in this design, consisting of empathize, define, ideate, prototype, and test. In the testing stage, for usability testing, task scenarios and Single Ease Question (SEQ) are used to measure effectiveness, efficiency, and user satisfaction. With an effectiveness of 94.4%, efficiency of 91.4%, and satisfaction of more than 6.2. User Experience Questionnaire (UEQ) is used to test interaction with the given solution design.